Mandibular canal measurements in relation to the lower first molar and base border of the mandible (Mustansiria Dental Journal, 2018)
The mandibular canal appears below or superimposed over the apices of themandibular molar teeth but it has some variations regarding its distance to both lowerfirst molar and the base border of the mandible that may make a problem specially forthe oral surgeon in his work during operations like implantation, so, this study wasdone to estimate the position of the mandibular canal and its relation to the lower firstmolar and the base border of the mandible by the aid of digital panoramicradiographs.The sample of this study was collected from patients who attended Al-Karamaspecialized center for dentistry. Forty patients were selected in this study with the agerange between 20-60 years (males and females) that divided in to four groupsaccording to a special criteria. Forty digital views (OPG) were taken for Iraqi patients,using computerized digital panoramic x-ray machine. All radiographs were examinedand then the position of the mandibular canal for each patient was estimated.The results revealed that the mandibular canal is most commonly located awayfrom the root apices of lower first molar, and the distance between the mandibularcanal and the base border of the mandible is indirectly proportional with age.